PTSD AND SELF-REGULATION AMONG INTERNALLY DISPLACED PERSONS IN BENUE STATE - Wanyima Atim, Stella; Sonter Anongo, Fredrick; E. Zamani, Andrew; Ayooluwa Afolabi, Olukayode (African Journal of Social and Behavioural Sciences, 2025)
Self-regulation is among the resiliency factors identified by most studies as a viable mechanism for managing traumatic events to achieve optimal psychosocial functioning and wellbeing. However, despite its relevance and the reported high rates of PTSD in Internally Displaced Persons (IDPs), including those in Benue state, studies examining the empirical link between these important variables are lacking. This research examined the influence of PTSD on self-regulation and its dimensions among internally displaced persons in Benue State. A cross- sectional survey design was adopted. A total of 384 Internally Displaced Persons (IDPs) were recruited from a population of 157,854 IDPs across four (4) local government areas of Benue state. A multi-stage sampling technique was employed, and the Raosoft online sample size calculator was used to determine the sample size. A standardised questionnaire containing measures of demographic variables, PTSD and Self-Regulation was administered to eligible participants. Multiple linear regression was utilised to analyse the research objective at the .05 level of significance. Findings revealed a significant influence of PTSD on self-regulation, accounting for 36.5% variance. Further results indicate that PTSD significantly and negatively impacted all the dimensions of self-discipline, impulse control, learning from mistakes and planning, with the tune of 57.6%, 43.6%, 30.4% and 16.9% contribution. The result of this study implies that PTSD has significantly impacted IDPs’ self-regulation, specifically posing difficulties in self-discipline, rational decision-making and planning. Therefore, early PTSD assessment and psychosocial support for IDPs are recommended to build resilience and achieve effective societal integration.